The neural bases of the learning and generalization of morphological inflection. (April 2017) - Nevat, Michael; Ullman, Michael T.; Eviatar, Zohar; Bitan, Tali
Abstract: Affixal inflectional morphology has been intensively examined as a model of productive aspects of language. Nevertheless, little is known about the neurocognition of the learning and generalization of affixal inflection, or the influence of certain factors that may affect these processes. In an event-related fMRI study, we examined the neurocognition of the learning and generalization of plural inflections in an artificial language, as well as the influence of both affix type frequency (the proportion of words receiving a given affix) and affix predictability (based on phonological cues in the stem). Adult participants were trained in three sessions, and were scanned after the first and last sessions while inflecting trained and untrained words. Untrained words yielded more activation than trained words in medial frontal (including pre-SMA) and left inferior frontal cortices, which have previously shown activation in compositional grammatical processing. A reliance on phonological cues for untrained word inflection correlated positively with pre-SMA activation, but negatively with activation in the pars triangularis. Thus, pre-SMA may be involved in phonological cue-based composition, while the pars triangularis underlies alternative processes. Inflecting trained items yielded activation in the caudate head bilaterally, only in the first session, consistent with a role for procedural memory in learning grammatical regularities. The medial frontal and left inferior regions activated by untrained items were also activated by trained items, but more weakly than untrained items, with weakest activation for trained-items taking the high-frequency affix. This suggests less involvement of compositional processes for inflecting trained than untrained items, and least of all for trained inflected forms with high-frequency affixes, consistent with the storage of such forms (e.g., in declarative memory). Overall, the findings further elucidate the neural bases of the learning and generalization of affixal morphology, and the roles of affix type frequency and affix phonological predictability in these processes. Moreover, the results support and further specify the declarative/procedural model, in particular in adult language learning. Highlights: Affixal inflection is a widely-examined model of productivity in language. This fMRI study probed the learning and generalization of affixal inflection. Adults were trained on affixal inflection in an artificial language. Activation in the caudate and frontal areas implicates procedural memory Affix frequency and affix phonological predictability modulated learning.